2006
DOI: 10.1097/01.psy.0000204923.09390.5b
|View full text |Cite
|
Sign up to set email alerts
|

Body Dissatisfaction in Women With Eating Disorders: Relationship to Early Separation Anxiety and Insecure Attachment

Abstract: Based on the cross-sectional findings of this study, insecure attachment appears to be a consistent correlate of negative body image evaluations in women with either anorexia nervosa or bulimia nervosa. If future prospective studies will confirm that an insecure style of attachment plays a role in promoting the development of body dissatisfaction, prevention and treatment of disordered eating pathology might be enhanced by focusing greater attention on attachment relationships.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
2

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(68 citation statements)
references
References 26 publications
3
60
0
2
Order By: Relevance
“…Esse temor faria com que tais indivíduos dependessem exageradamente da aprovação social e da aceitação dos outros, tornando--os mais sensíveis às mensagens da sociedade relacionadas à aparência e aos valores positivos associados à magreza (Troise, 2006). Em função dessa realidade, há uma preocupação em desenvolver programas preventivos de comportamentos alimentares anormais.…”
Section: Discussionunclassified
“…Esse temor faria com que tais indivíduos dependessem exageradamente da aprovação social e da aceitação dos outros, tornando--os mais sensíveis às mensagens da sociedade relacionadas à aparência e aos valores positivos associados à magreza (Troise, 2006). Em função dessa realidade, há uma preocupação em desenvolver programas preventivos de comportamentos alimentares anormais.…”
Section: Discussionunclassified
“…Attachment insecurity has been recognized in a variety of psychiatric disorders [20][21][22]. In eating disorders research there were some contrasting evidences about the association of attachment subtype with specific diagnosis, with some authors suggesting a link between attachment avoidance and anorexia nervosa and between attachment anxiety with bulimia nervosa.…”
Section: Methods and Methodological Issuesmentioning
confidence: 99%
“…Unhealthy dieting behaviors, such as fasting, purging, bingeing might even be developed, resulting in the buildup of eating disorder. In several studies, it was found that body dissatisfaction was consistently correlated with eating disorder in both male and female [19][20][21]. Dietary Restraint is a type of dieting aiming at weight reduction, as well as maintenance, by restriction of the types and amount of food choice [22].…”
Section: Pathway: Body Dissatisfaction -Dietary Restraintmentioning
confidence: 99%
“…There were over 43 millions of children estimated to be overweight and obese, as well as over 92 millions of children were at risk of overweight in 2010. In Hong Kong, the prevalence of overweight and obesity in primary school students had significantly increased as well, from 16.4% in 1997 to 21.4% in 2010 [4]. It is foreseeable that the trend will keep increasing and reach 9.1% or 60 million worldwide in 2020 [5].…”
Section: Introductionmentioning
confidence: 99%